2021
DOI: 10.5694/mja2.51153
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic medicine prescribing and polypharmacy for people with dementia entering residential aged care: the influence of changing general practitioners

Abstract: Objective: To examine relationships between changing general practitioner after entering residential aged care and overall medicines prescribing (including polypharmacy) and that of psychotropic medicines in particular.Design: Retrospective data linkage study. Setting, participants: 45 and Up Study participants in New SouthWales with dementia who were PBS concession card holders and entered permanent residential aged care during January 2010 -June 2014 and were alive six months after entry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Even though we report BPSD levels close to what is reported at admission to nursing homes [ 12 ], earlier work shows that prescription rates of antidepressants, antipsychotics, anxiolytics, sedatives, and hypnotics persistently increase during the first 6 months stay [ 12 , 46 , 51 ]. In our study, the use of these medications was not associated with dropout due to nursing home admission, while on the contrary, impaired functioning, dependency in activities of daily living, and BPSD were associated with nursing home admission.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Even though we report BPSD levels close to what is reported at admission to nursing homes [ 12 ], earlier work shows that prescription rates of antidepressants, antipsychotics, anxiolytics, sedatives, and hypnotics persistently increase during the first 6 months stay [ 12 , 46 , 51 ]. In our study, the use of these medications was not associated with dropout due to nursing home admission, while on the contrary, impaired functioning, dependency in activities of daily living, and BPSD were associated with nursing home admission.…”
Section: Discussionsupporting
confidence: 75%
“…A recent retrospective cohort study with a 1-year follow-up on 9324 patients with dementia in England concluded that higher continuity of GP care was associated with safer prescribing and lower rates of major adverse events [ 45 ]. Another retrospective study including 2250 new residents with dementia found that psychotropic drugs were dispensed at higher rates for those who changed GP when entering Australian residential care compared to those who continued seeing their regular GP [ 46 ]. This illustrates the importance of maintaining a continuous patient-GP relationship in preventing potentially inappropriate initiation of psychotropic medicines [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, these tools have not examined the risk profile of individuals at key periods in their aged care journey, including first entry into PRAC. This may be a particularly vulnerable period in terms of falls risk, with residents unfamiliar with their new surroundings, together with considerable changes to medication regimen and care [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The events leading to entry into an RACF (eg, major changes in health status) combined with the transition itself, which includes unfamiliarity with a new environment, new carers, changes in healthcare providers, medications and routines, can pose challenges to individuals, leading to poor health events after entering care. [6][7][8][9][10][11][12] Older individuals, especially those living in RACFs have frequent hospitalisations. 13 14 In Australia, 37% of RACF residents had at least one hospitalisation and 37% at least one emergency department (ED) presentation in 2018/2019.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%